The empress - Cast, Kristin (Cast, Kristin. Towerfall, 2025)
The Arcana aren't just figures in a tarot deck--they're real. Terrifyingly real. That's what I learned when I found a tarot card in the snow and was yanked from my world and into Towerfall. The first thing the people of this harsh, cruel realm did was try to kill me, and they probably would have succeeded if Kane hadn't taken me to his hideout in the woods and nursed me back to health. I don't know if I can trust him. He's too hot to be good news, he's definitely hiding secrets, and I've already seen him kill two people to protect me. If I hadn't just been helplessly dumped into his world, the blood on his sword and his dark, brooding mood would have me running in the opposite direction. But right now, convincing the Kingdom of Pentacles that Kane and I are married is my best chance of getting into the palace, and back to my own world. Because there's something wrong with Towerfall. Something deeply, deadly wrong. And if anyone finds out Kane and I aren't really husband and wife? Well, then both of us are dead. --